Coevaluation in the supervision of vocational training. The Inspector as a driver of a generative innovation process - Sánchez Ramón, Juan Miguel (Avances en Supervisión Educativa, 2016)
The General Plan of Action and Training Inspectorate course Education for 2015-2016, approved by Resolution 15/10/2015, by the Deputy Ministry of Education, Universities and Research of Castilla-La Mancha, establishes several priority actions, among which it is the "Monitoring student assessment process coursing teachings of Vocational Training in Castilla-La Mancha."In parallel to this performance inspection and in collaboration with the Department of Electricity of a Secondary School in the province of Albacete, the inspector poses an evaluative innovation center focused on an internal process of evaluation of teaching practice.
Keywords: inspection of education; supervision; co-evaluation; innovation